Media: Poder, Representação e Epistemologias. Diálogos a propósito da obra de Isabel Ferin da Cunha - Rita Figueiras (Investigação, 2019)
Inspired by the work of Isabel Ferin da Cunha and her applied research axes, researches and professors provide their contribution to the advancement of communication sciences. This book is shaped into three forms of dialogues: reflexive and theoretical, empirical and personal tributes.